A Sustainable Approach for Organisational using Strategic Management - Almazrouei, Abdulla; Md Yassin, Azlina (International Journal of Sustainable Construction Engineering and Technology, 2020)
Strategic management have gained popularity in the public institutions to foster good delivery service to the public. The strategic planning enables organizations to establish a strategic match between the internal competency, resources and external environment. Majority of the successful organizations across the world use strategic management and planning as a tool that enables to optimize the operations and achieve maximum productivity with the resources. This paper reviewed on strategic management for organisations in Abu Dhabi especially for Abu Dhabi Police (ADP) force.  It presents three strategic management theories which can be adopted by an organisation.  This would help the organisation such as police department to reduce the increasing crime rate and mortality rate in UAE.